The Body Politic - Aird, Catherine (London Pan Books, 1991)
Detective Inspector Sloan suspects murder when a tiny metal pellet is found in the cremated remains of Alan Ottershaw. Ottershaw died during the local Camulos Society's re-enactment of the Battle of Lewes. Sloan must look to history for the answer to the puzzle.
Keywords: Police -- Sloan, C. D. (Fictitious Character) -- England -- Engineers